2019
DOI: 10.1055/s-0039-1690207
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Diboron-Mediated Semireduction of Terminal Allenes

Abstract: A method for the regioselective reduction of the terminal double bond of 1,1-disubstituted allenes has been developed. In the presence of a palladium catalyst, tetrahydroxydiboron and stoichiometric water, allene semireduction proceeds in high yield to afford Z-alkenes selectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Other functional groups are reduced analogously by the Pd−H species [31] . Gates and Santos found that, in the presence of a palladium catalyst, THDB and water, allene semireduction proceeds in high yield to afford Z‐alkenes selectively [32] . Peng and Tang reported transfer hydrogenation from water to unsaturated carbonyls, quinones, and pyridinium salts forming the corresponding saturated carbonyls, dihydroxybenzenes, and hydropyridines by THDB/water in the absence of metal catalyst [33] …”
Section: Reductant Properties and Transfer Hydrogenation Of Water/thdbmentioning
confidence: 99%
“…Other functional groups are reduced analogously by the Pd−H species [31] . Gates and Santos found that, in the presence of a palladium catalyst, THDB and water, allene semireduction proceeds in high yield to afford Z‐alkenes selectively [32] . Peng and Tang reported transfer hydrogenation from water to unsaturated carbonyls, quinones, and pyridinium salts forming the corresponding saturated carbonyls, dihydroxybenzenes, and hydropyridines by THDB/water in the absence of metal catalyst [33] …”
Section: Reductant Properties and Transfer Hydrogenation Of Water/thdbmentioning
confidence: 99%
“…In 2019, the Santos group reported Pd/C catalyzed regioselective semireduction of the terminal allene of 1,1-disubstituted allenes in the presence of B 2 (OH) 4 and H 2 O (eq 31). …”
Section: Application Of H2 Evolution Upon Diborane Hydrolysismentioning
confidence: 99%